Penegakan Hukum Dalam Perspektif Hukum Progresif - Ufran (Perspektif Hukum, 2019)
The Failure to enforce law and justice will be one of the factors of social dis-integration. If it is responded well and systematically it will be a threat to a country's failure. These initial symptoms can be seen from the emergence of various vigilante acts. The empty spaces filled with violence are caused by the vacuum of law. The law fails to do its job to solve social problems that arise. The explanation in this paper seeks to analyze the root problem of the failure of law enforcement in Indonesia seen in the perspective of the legal system by Friedman. To analyze the solution, the perspective used is an analysis of the style of progressive law as stated by Satjipto Rahardjo. The use of these two perspectives is expected to be able to describe well the real fundamental problem in our current law enforcement